Evidence of acute inflammation in the periodontal ligament subsequent to orthodontic tooth movement in rats - Cooper Stephanie M.; Sims Milton R. (Sciendo, 1989)
Experimental orthodontic tooth extrusion can result in red cell diapedesis through the PDL vascular wall. Diapedesis is an early sign of acute inflammation. At the ultrastructural level, red cell migration is demonstrated occurring through the endothelial junction of a postcapillary-sized venule. This phenomenon is considered to be indicative of unphysiological tooth loading..